India : The Challenges of Development, A Country Assistance Evaluation - Zanini, Gianni (Washington, DC: World Bank, 2013)
This country assitance evaluation assesses the development effectiveness of World Bank assistance to India during the 1990s. The Bank has been India's largest source of external long-term capital and has financed a sizable share of its public investment. Its lending and nonlending services have been thinly spread over many central and state agencies and have addressed many different objectives. Overall the strategic goals of the Bank during the decade were relevant and the design of the assitance strategy improved. Efficacy is rated as modest, mainly because of the Bank's limited impact on fiscal and other structural reforms, the failure to develop an effective assistance strategy for rural poverty reduction, and the mediocre quality of projects at exit. Institutional development impact has also been modest and sustainability incertain, given the serious remaining fiscal imbalances, high environmental costs, and governance weaknesses. Taken together, these ratings gauge the overall outcome of assistance for the decade as moderately satisfactory. But these ratings must be viewed in light of the recent, subtantial improvement in the relevance of the assistance strategy, largely prompted by the innovations embodied in the 1997 Country Assistance Strategy (CAS). The focus on poverty reduction has been sharpened, a more selective approach to state assistance put in place, and greater attention given to governance and institutions, although it is still too early to judge efficacy.